Limit Cycles Bifurcated from Some Z4-Equivariant Quintic Near-Hamiltonian Systems - Simin Qu; Cangxin Tang; Fengli Huang; Xianbo Sun (Abstract and Applied Analysis)
We study the number and distribution of limit cycles of some planar Z4-equivariant quintic near-Hamiltonian systems. By the theories of Hopf and heteroclinic bifurcation, it is proved that the perturbed system can have 24 limit cycles with some new distributions. The configurations of limit cycles obtained in this paper are new.